Extreme Vertices of the Psi-Divisible Graph of the Group Z_{p^n} - Kumar, Amit; Kumar, Vinod; Sehgal, Amit (Journal of the Indonesian Mathematical Society, 2026)
The $Ψ$-divisible graph of a finite group $G$, denoted by $Ψ_G$ is a special type of simple undirected graph, in which the set of vertices contains non-trivial subgroups of $G$ and two distinct vertices $u$ and $v$ are adjacent if and only if $u$ is a proper subgroup of $v$ such that $Ψ(u)|Ψ(v)$ or $v$ is a proper subgroup of $u$ such that $Ψ(v)|Ψ(u)$. The existence of extreme vertices in the $Ψ$-divisible graph of the finite cyclic group $\mathbb{Z}_{p^n}$ is described in this article.